Oxidative Stress and Inflammatory Modulation of Ca2+ Handling in Metabolic HFpEF-Related Left Atrial Cardiomyopathy - David Bode; Yan Wen; Niklas Hegemann; Uwe Primessnig; Abdul Parwani; Leif-Hendrik Boldt; Burkert M. Pieske; Frank R. Heinzel; Felix Hohendanner (MDPI AG, 2020)
Metabolic syndrome-mediated heart failure with preserved ejection fraction (HFpEF) is commonly accompanied by left atrial (LA) cardiomyopathy, significantly affecting morbidity and mortality. We evaluate the role of reactive oxygen species (ROS) and intrinsic inflammation (TNF-α, IL-10) related to dysfunctional Ca2+ homeostasis of LA cardiomyocytes in a rat model of metabolic HFpEF. ZFS-1 obese rats showed features of HFpEF and atrial cardiomyopathy in vivo: increased left ventricular (LV) mass, E/e' and LA size and preserved LV ejection fraction. In vitro, LA cardiomyocytes exhibited more mitochondrial-fission (MitoTracker) and ROS-production (H2DCF). In wildtype (WT), pro-inflammatory TNF-α impaired cellular Ca2+ homeostasis, while anti-inflammatory IL-10 had no notable effect (confocal microscopy; Fluo-4). In HFpEF, TNF-α had no effect on Ca2+ homeostasis associated with decreased TNF-α receptor expression (western blot). In addition, IL-10 substantially improved Ca2+ release and reuptake, while IL-10 receptor-1 expression was unaltered. Oxidative stress in metabolic syndrome mediated LA cardiomyopathy was increased and anti-inflammatory treatment positively affected dysfunctional Ca2+ homeostasis. Our data indicates, that patients with HFpEF-related LA dysfunction might profit from IL-10 targeted therapy, which should be further explored in preclinical trials.